Adolescent Exposure to the Synthetic Cannabinoid WIN 55212-2 Modifies Cocaine Withdrawal Symptoms in Adult Mice - Aguilar, María A. (Int J Mol Sci, 2017)
Chronic cannabinoid consumption is an increasingly common behavior among teenagers and has been shown to cause long-lasting neurobehavioral alterations. Besides, it has been demonstrated that cocaine addiction in adulthood is highly correlated with cannabis abuse during adolescence. Cocaine consumption and subsequent abstinence from it can cause psychiatric symptoms, such as psychosis, cognitive impairment, anxiety, and depression. The aim of the present research was to study the consequences of adolescent exposure to cannabis on the psychiatric-like effects promoted by cocaine withdrawal in adult mice. We pre-treated juvenile mice with the cannabinoid CB1 receptor agonist WIN 55212-2 (WIN) and then subjected them to a chronic cocaine treatment during adulthood. Following these treatments, animals were tested under cocaine withdrawal in the following paradigms: pre-pulse inhibition, object recognition, elevated plus maze, and tail suspension. The long-term psychotic-like actions induced by WIN were not modified after cocaine cessation. Moreover, the memory impairments induced by cocaine withdrawal were not altered by previous adolescent WIN intake. However, WIN pre-treatment prevented the anxiogenic effects observed after cocaine abstinence, and led to greater depressive-like symptoms following cocaine removal in adulthood. This study is the first to show the long-lasting behavioral consequences of juvenile exposure to WIN on cocaine withdrawal in adult mice.